Effects of defibrotide on stress-induced bladder morphology - (:unkn) unknown (My University, 1999)
Objective: This study investigates the morphological effect of defibrotide on cold-immobilization stress-induced rat urinary bladder. Material and Methods: Wistar albino rats were used in this study. After the cold, immobilization stress following the 48 hours of fasting, defibrotide was applied either intraperitonally (16 mg/ml) or intravesically (1200 μg/ml). Urinary bladders were removed for light and electron microscopical investigations. Results: The stress group showed leukocyte infiltration and edema, further vacuoles in the cytoplasm of urothelial cells and loose tight junctions. Additionally, urothelial protrusions towards the lumen were observed. The defibrotide-applied groups displayed regular morphology both under light and electron microscopy level. Conclusion: These results showed that defibrotide reverse the stress induced morphological alterations. Although the biochemical effects of defibrotide is unknown, a possible explanation could be via modulation of calcium entry into the cells, and increase the permeability and regulation of inflammatory response and/or may have a role in the protection of urothelium by increasing the synthesis of prostaglandins and have a cytoprotective role in stress-induced bladder damage.
Keywords: Cold-immobilization stress; Cytoprotection; Defibrotide; Ultrastructure; Urinary bladder